1998
DOI: 10.1101/gad.12.20.3156
|View full text |Cite
|
Sign up to set email alerts
|

Fgf-10 is required for both limb and lung development and exhibits striking functional similarity to Drosophila branchless

Abstract: Fgf-10-deficient mice (Fgf-10−/− ) were generated to determine the role(s) of Fgf-10 in vertebrate development. Limb bud initiation was abolished in Fgf-10 −/− mice. Strikingly, Fgf-10 −/− fetuses continued to develop until birth, despite the complete absence of both fore-and hindlimbs. Fgf-10 is necessary for apical ectodermal ridge (AER) formation and acts epistatically upstream of Fgf-8, the earliest known AER marker in mice. Fgf-10 −/− mice exhibited perinatal lethality associated with complete absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
671
2
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 824 publications
(703 citation statements)
references
References 42 publications
27
671
2
3
Order By: Relevance
“…This observation suggests that Fgf10 may serve as a mesenchyme factor for eyelid formation. Indeed, Fgf10 knockout embryos exhibit similar eyelid defects to those found in Fgfr2 ⌬III/⌬III mutant embryos (Min et al, 1998;Sekine et al, 1999). Fgf8 has been identified as a key factor in limb development; however, our in situ hybridization suggests that Fgf8 is unlikely to be essential for eyelid initiation as it is expressed at very low levels during early stages of eyelid development (data not shown).…”
Section: Discussionmentioning
confidence: 59%
“…This observation suggests that Fgf10 may serve as a mesenchyme factor for eyelid formation. Indeed, Fgf10 knockout embryos exhibit similar eyelid defects to those found in Fgfr2 ⌬III/⌬III mutant embryos (Min et al, 1998;Sekine et al, 1999). Fgf8 has been identified as a key factor in limb development; however, our in situ hybridization suggests that Fgf8 is unlikely to be essential for eyelid initiation as it is expressed at very low levels during early stages of eyelid development (data not shown).…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, expression of the gene encoding the receptor of Fgf10, Fgfr2IIIb, was detected in the overlaying epidermis and some populations of the underlying mesenchyme of the wing membrane primordia and in the limb epidermis, including the AER. In vertebrates, maintenance of proximodistal outgrowth of the embryonic limbs requires Fgf10 in the mesenchyme to activate Fgf8 in the AER, which in turn promotes mesenchymal outgrowth 18,[34][35][36] . It appears that the outgrowths of the anterior, lateral and interfemoral wing membranes formed in bat embryos are achieved by a molecular mechanism that is partly different from that regulating the outgrowth of the limb.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it plays a key role in the distal lung, promoting outgrowth of epithelial buds (Bellusci et al, 1997;Min et al, 1998;Sekine et al, 1999;Weaver et al, 2000). We have found that in Fgf10 heterozygotes fewer SMGs are formed, and these do not undergo branching morphogenesis to their full extent.…”
Section: Discussionmentioning
confidence: 99%